2001
DOI: 10.1002/1097-4636(20011215)57:4<477::aid-jbm1193>3.0.co;2-5
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced osteobonding by negative surface charges of electrically polarized hydroxyapatite

Abstract: Negative surface charges of electrically polarized hydroxyapatite ceramics have been proven to enhance osteobonding in canine bone tissues. Even in a wide gap of 0.2 mm between hydroxyapatite and bone, the negatively charged hydroxyapatite conducted formation of unidirectionally oriented bone layer into direct contact with the hydroxyapatite surface 7 days after implantation. By day 14, the gap was filled with maturing bones linked to each other while conventional hydroxyapatite required at least 28 days for d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
157
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
5
5

Relationship

3
7

Authors

Journals

citations
Cited by 225 publications
(159 citation statements)
references
References 32 publications
2
157
0
Order By: Relevance
“…Even in wide gaps of 0.2-0.5 mm between the HA and bone, direct bonding bone formation was observed on the negatively charged surfaces at 1 week after implantation. 6 In the vicinity of the positively charged HA surfaces, the formation of bone derived from osteoid tissue entirely occupied the gaps. 7 Within 4 weeks, almost perfect bone reconstruction occurred accompanied with activated osteoblastic cells, with the processes varying according to the charge polarity.…”
Section: Introductionmentioning
confidence: 99%
“…Even in wide gaps of 0.2-0.5 mm between the HA and bone, direct bonding bone formation was observed on the negatively charged surfaces at 1 week after implantation. 6 In the vicinity of the positively charged HA surfaces, the formation of bone derived from osteoid tissue entirely occupied the gaps. 7 Within 4 weeks, almost perfect bone reconstruction occurred accompanied with activated osteoblastic cells, with the processes varying according to the charge polarity.…”
Section: Introductionmentioning
confidence: 99%
“…Polarization is important in biomaterials, since we have more recently demonstrated by in vitro and in vivo tests that the charged surfaces of electrically polarized hydroxyapatite 9,10 acquired enhanced osteoconductivities. [11][12][13] This study will demonstrate the electrical polarizability and in vitro biocompatibility or chemico-vector effect of gc: Narpsio.…”
Section: -7mentioning
confidence: 93%
“…So the effect of piezoelectricity of hydroxyapatite would be cancelled out and seems to be minor compared to that of collagen fibrils. In 2001, however, Dr. K. Yamashita found that the negative charge introduced in hydroxyapatite induced the growth of new bone [37], To study the molecular mechanism how the electromechanical properties of collagen and hydroxyapatite influence on the growth of bone is a challenging subject of future research. The Wolff's law connecting the mechanical stress and the direction of growth of bone is also a good target of research.…”
Section: Piezoelectricity Of Synthetic Polymersmentioning
confidence: 99%